Emergent syntax for conversation clausal patterns and the organization of action - Maschler, Yael; Doehler, Simona Pekarek; Lindström, Jan, 1964-; Keevallik, Leelo (Studies in language and social interaction ;, 2019)
"This volume explores how emergent patterns of complex syntax - that is, syntactic structures beyond a simple clause - relate to the local contingencies of action formation in social interaction. It examines both the on-line emergence of clause-combining patterns as they are 'patched together' on the fly, as well as their routinization and sedimentation into new grammatical patterns across a range of languages - English, Estonian, Finnish, French, German, Hebrew, Italian, Mandarin, and Swedish. The chapters investigate how the real-time organization of complex syntax relates to the unfolding of turns and actions, focusing on: (i) how complex syntactic patterns, or routinized fragments of 'canonical' patterns, serve as resources for projection, (ii) how complex syntactic patterns emerge incrementally, moment-by-moment, out of the real-time trajectories of action, (iii) how formal variants of such patterns relate to social action, and (iv) how all of these play out within the multimodal ecologies of action formation. The empirical findings presented in this volume lend support to a conception of complex syntax as fundamentally temporal, emergent, dialogic, sensitive to local interactional contingencies, and interwoven with other semiotic resources"--